The impact of symptoms on daily life as perceived by patients with Charcot-Marie-Tooth type 1A disease - Tozza, Stefano; Bruzzese, Dario; Severi, Daniele; Spina, Emanuele; Iodice, Rosa; Ruggiero, Lucia; Dubbioso, Raffaele; Iovino, Aniello; Aruta, Francesco; Nolano, Maria; Santoro, Lucio; Manganelli, Fiore (Neurological sciences, 2022)
Introduction In Charcot-Marie-Tooth type 1A (CMT1A) patients, daily life is mainly influenced by mobility and ambulation dysfunctions. The aim of our work was to evaluate the perception of disturbances that mostly impact on daily life in CMT1A patients and its difference on the basis of age, gender, disability, and quality of life. Methods Forty-one CMT1A patients underwent neurological assessment focused on establishing clinical disability through the Charcot-Marie-Tooth Neuropathy Score (CMTNS) and quality of life through the Short Form-36 (SF-36) questionnaire. We identified from CMT disturbances 5 categories [weakness in lower limbs (WLL), weakness in upper limbs (WUL), skeletal deformities (SD), sensory symptoms (SS), balance (B)] and patients classified the categories from the highest to the lowest impact on daily life (1: highest; 5: lowest). Ranking of the 5 categories, in the overall sample and in the different subgroups (dividing by gender, median of age and disease duration, CMTNS, domains of SF-36), was obtained and differences among subgroups were assessed using a bootstrap approach. Results Rank analysis showed that WLL was the most important disturbance on daily life whereas WUL had the lowest impact. In the older CMT1A group, the most important disturbance on daily life was B that was also the most relevant disturbance in patients with a greater disability. SD influenced daily life in younger patients. SS had less impact on daily life, with the exception of patients with a milder disability. Discussion Our findings demonstrated that the perception of disturbances that mostly impact on CMT1A patients’ daily life changes over the lifetime and with degree of disability.